Pengaruh Inovasi Produk dan Kualitas Produk terhadap Keunggulan Bersaing dengan di Mediasi Kepuasan Konsumen pada Toko Roti dan Kue Onoydi Kota Jambi - Nur Vironika; Dahmiri Dahmiri; Sigit Indrawijaya (JURNAL RISET MANAJEMEN (JURMA), 2024)
Micro, Small and Medium Enterprises (UMKM play an important role in economic activities because they dominate the economic structure in Indonesia. In increasingly tight competition, a business must have strong competitiveness to create competitive advantages with other businesses, especially businesses in the culinary sector such as bread and cakes in Jambi City. Many factors determine competitive advantage, one of which is product innovation and product quality. The aim of this research is to analyze the influence of product innovation and product quality on competitive advantage mediated by consumer satisfaction at onoy bakeries and cakes in Jambi City. This research uses descriptive methods and a quantitative approach. The sampling method uses a purposive sampling technique. The number of samples in this research was 80 respondents. The data used is primary data obtained through a questionnaire using a Google form with a Likert scale. The data analysis method in this research uses the Structural Equation Model (SEM) technique using the SmartPLS program (v.4.0.9.9) for Windows. The results of this research show that product innovation and product quality have a positive and significant effect on competitive advantage mediated by consumer satisfaction.